Vulnerability assessment of the power grid against progressing wildfires. (April 2015) - Choobineh, Moein; Ansari, Bananeh; Mohagheghi, Salman
Abstract: Wildfires are common in many forest and grassland ecosystems. Power transmission lines are vulnerable to wildfires in their vicinity, mainly due to increased conductor temperatures as a result of heat released by the fire. This may damage the conductor and lead to violation of safety clearances between conductor and ground. To address the situation, a power system operator may dynamically alter the ratings of the lines in the affected areas to reduce the current flowing through them, thereby assisting with conductor cooling. A unified model is proposed here that allows for dynamically changing the thermal ratings of conductors in the vicinity of a wildfire. The proposed model incorporates the radiative and convective heat released due to a progressing wildfire into the conductor thermal rating calculation in order to derive the updated conductor rating. Case studies are presented to show the effects of a progressing wildfire on a power system. It is shown that dynamically changing the ratings of power lines changes the flow of power through the network, moving the system towards a sub-optimal operating point. Under heavy loading conditions, this may even lead to imbalance between load and generation, therefore forcing involuntary load shedding to avoid system collapse. Highlights: Wildfires affect the available capacity of transmission lines in their vicinity. A model is proposed to calculate dynamic rating of lines exposed to wildfire. We modify line rating based on the heat released by a progressing wildfire. If line rating is not modified, heat may result in line damage and safety issues. Updated line rating leads to suboptimal operating point for the power system.